Bioinspired Gas‐Confined Hollow Microfiber with 2D Conducting Polymer/Graphene Skeleton for Ultrasensitive Liquid Environment Sensor. Issue 24 (12th November 2021) - Zou, Xuejing; Jiang, Qianqian; Wang, Xusheng; He, Yonglin; Chai, Yuqiao; Ma, Hui; Ma, Xinlei; Wang, Yapei; Xue, Mianqi
Abstract: Due to the strong liquid intermolecular force, feasible sensing‐detection methods in liquid environments are absent. Inspired by fish swim bladder, herein, a hollow‐structured microfiber is designed to realize high‐performance sensing in liquid environments. It composes of 2D polypyrrole (2DPPy) and reduced graphene oxide (rGO), and its wall has a porous skeleton of 2DPPy/rGO/2DPPy (2DPrG2DP). The internal cavities of porous skeleton will be filled by the liquid, while leaving a bubble inside the hollow micropipe due to the liquid surface tension, thus forming a solid/liquid/gas triple‐phase interface. This hollow microfiber transforms the unmanageable liquid‐phase sensing into gas‐phase sensing. During this process, the good mechanical strength of 2DPPy enables the high sensing operability, and the reversible gas extrusion‐withdraw process enables the high sensitivity. The hollow 2DPrG2DP microfiber‐based sensor can be potentially used to machine trouble shooting, water level monitoring, ocean current monitoring, tsunami warning, body fluid and blood monitoring, and oil transportation monitoring. Abstract : A hydrophobic hollow microfiber, with a tough framework of reduced graphene oxide and highly‐oriented polypyrrole and a stable inner gas microcolumn, is designed to solve unmanageable liquid‐environment sensing by transforming sluggish expelling‐injection process of liquid into easy extrusion‐rebound of restricted gas microcolumn. Its great sensing sensitivity, resolution, and mechanical strength enable high universality in various liquid application scenarios.